If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(12v+11)+30=16v+6
We move all terms to the left:
(12v+11)+30-(16v+6)=0
We get rid of parentheses
12v-16v+11-6+30=0
We add all the numbers together, and all the variables
-4v+35=0
We move all terms containing v to the left, all other terms to the right
-4v=-35
v=-35/-4
v=8+3/4
| 9s-7=1+10s | | -8-x=-3(2x-4)+3x | | -2/3c+3=5c+1/2 | | 46-3x=16+12x | | -4x+7=-10x+30 | | 4x-3(-2)=10 | | 5(x-2)=3(3x+4) | | 40+19a=30a-19 | | 3/4x+22=220 | | 14=w/6 | | 8+6y=-4 | | 2x-11/2=8 | | 28-x=3x+42 | | (5/3)j-6=94 | | 2b^2-5b=18 | | 38/19=m-5/20 | | -3/2(4x+7)=6x+8 | | 4(m+2)+1=17 | | -10-7x=-4-5x | | t/4+16=t/2+4 | | 2y+2y+17+5=180 | | 8a-6=-86 | | -34+9x=97 | | 20=3(h+3)+2 | | 1+x/16=0 | | -42.12=-7.8x | | 4(y+2)-5=15 | | (x-7)/7=7(7x-49) | | -22-3x=17 | | 5r/9=1/2 | | -8x-27=37 | | 40=0.10(x-100) |